Marketing channels in value creation and delivery of cheese in the Republic of Serbia - Petković, Goran; Užar, Dubravka (Anali Ekonomskog fakulteta u Subotici, 2020)
Although the use of various forms of marketing channels is increasing within agricultural marketing, there have been only a limited number of research efforts exploring the influencing factors on the structure of agricultural marketing channels and the decisions to select individual intermediaries. Due to the specific nature of agricultural production and its products, complex transportation and storage problems require a greater number of intermediaries in their movement from producer to consumer. Management of sales channels is an important factor for the success of farmers, so it is necessary to evaluate the impact of changes in the environment on them. In order to adapt sales to the demands of the contemporary market, cheese producers are faced with the dilemma of expanding existing sales channels, adding modern channels to existing traditional channels, or making more radical changes to the market. This paper defines the distribution methods and key players in cheese delivery that should point to strengthening the competitiveness of producers in the global market.